Assessing the role of artificial compaction on physicochemical properties and carbon emissions of tropical peat soils - Samuel, Marshall Kana (2020)
Compaction is undertaken because of claims that confined and restricted peat pores may enhance soil moisture due to the effect of capillary rise. The increase in soil moisture is said to lead to additional benefits of reduced C emissions and reduced risk and extent of peat fires. Nevertheless, information pertaining to induce compaction on peat physicochemical properties and carbon emission seems to be in scarcity. This thesis explored the notion of a misconception in definition of peat compaction in tropical peatland landscape due to confounding factors between (passive) natural compaction by oxidation, shrinkage and compression and (active) artificial compaction- by heavy machinery. This study suggest that this could be a reason for wide interpretation on peat compaction processes. Therefore, the aim of this research project was to assess the impact of artificial compaction on the tropical peat physicochemical properties and carbon emissions from peat surface as well through peat fire.